An improvement of synchronously rotating reference frame based voltage sag detection for voltage sag compensation applications under distorted grid voltages - Sillapawicharn,Y. (2015)
An improvement of synchronously rotating reference frame based voltage sag detection for voltage sag compensation applications under distorted grid voltages is proposed. The voltage sag detection is the one of important parts in the voltage sag compensation processes. In the past, the conventional synchronously rotating reference frame (CSRRF) based voltage sag detection is widely used in the voltage sag compensation applications. Its disadvantage is a long delay of detection time. This means the next process initiation of voltage sag compensation is also delayed, and then the load voltage can be affected from voltage sag. The modified synchronously rotating reference frame (MSRRF) based voltage sag detection is able to detect the voltage sag in a short delay of detection time by differentiator employment. However, its operation under the distorted grid voltages condition is unavailable because of the sensitivity of differentiator action to the high frequency components that caused by voltage harmonic. This paper proposed the improvement of MSRRF based voltage sag detection under distorted grid voltages. The operation of proposed improved MSRRF, MSRRF, and CSRRF based voltage sag detections are investigated via computer simulation to verify the advantage of proposed voltage sag detection. © 2011 IEEE.